The creative approach of the South African advertising industry towards the black consumer - Carla Enslin (Communicare)
Successful advertising emerges as a creative and effective communication strategy. When advertising to the diverse South African black consumer markets, the creative team must be familiar with the values, needs and aspirations of the potential consumer and their creative ability to effectively act upon the value system of the consumer realises in the design of the advertising message. This article concentrates on the findings of a qualitative research study to investigate the creative approach of the South African advertising industry towards the black consumer. The need for a receiver oriented creative perspective is established and reinforced through the design of two communication models which high light practical guidelines to be implemented by the advertising industry